The World's First Full Press Freedom The Radical Experiment of Denmark-Norway 1770-1773 - Langen, Ulrik (De Gruyter, 2022)
The book investigates the world's first full legal press freedom. In 1770, king Christian 7's physician, the German enlightener J.F. Struensee, effectively became ruler of Denmark. His first decree, complete abandonment of censorship, led to 3 years of press freedom and an avalanche of pamphlets and debates. In early 1772, a coup led to his execution, giving rise to European outcry and fascination with the radical political experiment of Denmark.